Choice of Electrical Generator for Small Wind Turbines - Bùi, Văn Hồng (Journal of Technical Education Science, 2010)
A permanent magnet generator has a simple structure, easy to operate, and is used for small wind turbines. Because their speed is always changing, so the energy is stored in the battery to ensure quality of power. Experiments on the physical model have shown that the energy performance depends on the number and diameter of the wires, and the operation mode of the generatorsA permanent magnet generator has a simple structure, easy to operate, and is used for small wind turbines. Because their speed is always changing, so the energy is stored in the battery to ensure quality of power. Experiments on the physical model have shown that the energy performance depends on the number and diameter of the wires, and the operation mode of the generators